Effects of social constructivist teaching methods on EFL students’ reading comprehension and teamwork skills in Ethiopia - Addis Kebede Adere; Reda Darge Negasi; Amare Sahile Abebe (Cogent Education)
The study aimed to determine the effect of integrated social constructivist teaching methods, including problem-basedlearning, cooperative learning, collaborative learning, and scaffolding, on the reading comprehension (RC) andteamwork skills of Grade 8 English as a Foreign Language (EFL) students. The study employed a quasiexperimentaldesign that embraced pretest and posttest group comparison. The sample population was 64 (33 Mand 31 F) Grade 8 students from two sections at Shashemane Primary School in the 2021/22 academic year. Thestudy used a lottery method to randomly divide the participants into experimental and control groups. An independentsamples t-test was performed to determine whether there were statistically significant inter-group mean scoredifferences on the RC pretest and posttest, and the gain differences. Data on students’ teamwork skills werecollected through class observations, focus group discussions (FGDs), interviews, and post-observation discussions.The posttest results revealed that the intervention improved the RC skills of the experimental group. The comparisonof the gain differences between the pretest and posttest scores showed that the experimental group outdid thecontrol group significantly. Similarly, the intervention brought improvement in the teamwork skills of students in theexperimental group. Recommendations are given based on the study’s findings.